y=-cos2(x-pi/12)

= -sin2(x-pi/12+3pi/12)

= -sin2(x+pi/6)

I don't understand how you get the3pi/12.If there is another simpler way to get the same answer, please include it.=]

Printable View

- June 16th 2008, 05:43 PMjohettin need of a quick response...cos-->sin equation
y=-cos2(x-pi/12)

= -sin2(x-pi/12+**3pi/12**)

= -sin2(x+pi/6)

I don't understand how you get the**3pi/12.**If there is another simpler way to get the same answer, please include it.=] - June 16th 2008, 07:49 PMo_O
This uses the identity:

So looking at your expression:

(Factored out a 2 of the inside expression)

etc. etc.